Solving global problems: Waste to power while creating stakeholder shared value - Thaspong Chailertpong; Thepparat Phimolsathien (My University, 2018)
In 2015, an estimated 1.2 billion people, or 16% of the global population, did not have access to electricity.At the same time, solid waste generation rates have risen fast, reaching 30 million tons in 1980, 200 million tons today, and projected to exceed over 11 million tons per day by 2100.The waste from cities alone is already enough to fill a line of trash trucks 5,000 kilometers long every day.Solutions, therefore, must be found, with Waste to Energy (WtE) conversion a strong contender, which presently represents a $29 billion industry globally.By use of cluster sampling, a sample of 361 individuals was surveyed by use of a 63-item, Likert-type agreement scale questionnaire on the study's four constructs.A confirmatory factor analysis was run prior to the structural equation model, with analysis undertaken by use of LISREL 9.1.All causal factors in the model were shown to have a positive influence on the creation of shared value (CSV) of the waste management power plant and the local community, with 68% of the variance of the factor affecting CSV (R2).Ranked in importance, the three latent variables were government policy (GP), the waste management power plant (WMPP), and community participation (CP), with a total score of 0.83, 0.37 and 0.36, respectively.
Keywords: Value (mathematics); Sustainable Building Design and Assessment